2023
DOI: 10.1037/drm0000202
|View full text |Cite
|
Sign up to set email alerts
|

The feeling priming theory (FPT) of dreaming.

Abstract: This article presents the feeling priming theory (FPT) of dreaming. According to the FPT, dreaming favors the motivation to avoid aversive anticipated events and to approach gratifying anticipated events. It is suggested that one component of anticipated emotions-anticipated feelings-is reproduced in dreams. Upon awakening and during the day, these anticipated feelings would remain activated (primed) in memory. Consequently, anticipated emotions would exert a greater influence on avoidance and approach behavio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 273 publications
(474 reference statements)
2
4
0
Order By: Relevance
“…In partial support of our third prediction, we observed that the discrepancy between the evaluation of positive emotions in the dream between the subject and the judge, termed as subjects' positivity bias, played a positive role in morning emotions, supporting the emotion regulation function theories of dreams (Perlis and Nielsen, 1993;Malinowski et al, 2019). The positive relationship observed between the subject's dream positivity bias and positive morning emotions may also be attributed to the feeling priming effect postulated by the Feeling Priming Theory (FPT; Lemyre et al, 2022) of dreams. According to FPT, feelings felt in dreams may be associated with feelings felt in waking due to the continued activation of dream feelings, in this case, heightened subjective perception of positive emotions, in memory during the postsleep period (Lemyre et al, 2022).…”
Section: Discussionsupporting
confidence: 72%
See 4 more Smart Citations
“…In partial support of our third prediction, we observed that the discrepancy between the evaluation of positive emotions in the dream between the subject and the judge, termed as subjects' positivity bias, played a positive role in morning emotions, supporting the emotion regulation function theories of dreams (Perlis and Nielsen, 1993;Malinowski et al, 2019). The positive relationship observed between the subject's dream positivity bias and positive morning emotions may also be attributed to the feeling priming effect postulated by the Feeling Priming Theory (FPT; Lemyre et al, 2022) of dreams. According to FPT, feelings felt in dreams may be associated with feelings felt in waking due to the continued activation of dream feelings, in this case, heightened subjective perception of positive emotions, in memory during the postsleep period (Lemyre et al, 2022).…”
Section: Discussionsupporting
confidence: 72%
“…This finding is intriguing and suggests several phenomena at play. First, as seen in previous research, this difference could suggest that judges have 10.3389/fnbeh.2022.947396 more difficulty evaluating the positive emotions experienced by the dreamer in their dream narrative (Sikka et al, 2017;Lemyre et al, 2022). Interestingly, we did not find a correlation between the word length of the dream report and the degree of the subject's positivity bias, potentially suggesting that the positivity bias is not created by methodological artifact but rather may represent an adaptive psychological response.…”
Section: Discussionsupporting
confidence: 61%
See 3 more Smart Citations